Player selection procedures in team sport games - Trninic, S.; Papic, V.; Trninic, V.; Vukicevic, D. (Acta Kinesiologica, 2008)
Attention is focused on the fact that talent identification, players' potential determination, selection of players for certain teams, as well as a design and application of developmental training programmes, aimed at the improvement of actual play quality, are the most important coach's duties which simultaneously determine the development of a particular sport game on a global level. Since players are the carriers of play concepts and the producers of competition achievements, their selection is a fundamental goal of professional work in sports clubs. The assumed future development of sports games will probably erase the strict differences among the basic play positions, but roles and tasks will remain crucial components of technical-tactical activities players are bound to perform when playing a particular post. Due to their obligation to take over the responsibility to play various roles in different phases of the game, the players must adopt and perfect universal technical-tactical skills and knowledge (polyvalence). Play roles are dynamic, probably growing even ever more dynamic. They depend on the momentary position of the ball, on the position of the team-mates and the opponents on the court, and on the play phase and concepts of play. In the selection of players the application of objective, scientifically founded methods is indispensable. Unfortunately, contemporary developmental level of kinesiology does not allow entirely objective exploration of players as biological, psychological and sociological entities. Therefore, it is necessary to analytically dissolve the sport potential of a player (the basic and specific anthropological characteristics) and his/her actual play quality into a series of measurable and non-measurable components.